Upaya Pengurangan Hama Tumbuhan Melalui Program Pembuatan Pestisida Nabati di Jorong Aie Karuah Nagari Salimpek Kabupaten Solok - Fitra, Halkadri; Dwi Zulfi, Fara; Amelia Cahyati, Suci; Aminarti, Aminarti; Suhandai, Imel; Tsani, Raihan (Manaruko: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to educate and empower the residents of Jorong Aie Karuah, Nagari Salimpek, Lembah Gumanti Subdistrict, Solok Regency in reducing plant pests through the production and application of botanical pesticides. The main issue faced by local farmers is the high incidence of pest attacks and their dependence on chemical pesticides, which have negative impacts on the environment and human health. The program was conducted through counseling sessions, training, and hands-on practice in making botanical pesticides using natural ingredients such as soursop leaves, garlic, and lemongrass. The results of the activity showed strong community enthusiasm and an initial adoption of botanical pesticides in local farming practices. This initiative is expected to raise awareness of environmentally friendly agriculture and help reduce production costs for farmers. Furthermore, the program supports the community’s self-reliance in addressing agricultural problems sustainably